Fenomena Bullwhip Effect pada Supply Chain dan Struktur Tata Kelola Perguruan Tinggi - Farham HM. Saleh (Unisia, 2008)
Bullwhip effect is the phenomenon in which information on demand is distorted while movingupstream along supply chain. This causes a variance of demand to be amplified.Generally, researches about the bullwhip effect are conducted in supply chain of goodsindustries, and not in that of service industries. To what extent is the bullwhip effect possiblein service industries, especially in university governance? This research has beenconducted to analyze whether the bullwhip effect may happen in university governance.This research has revealed that subject to a specific condition, a similar bullwhip effectphenomenon may happen in university governance.Keywords: bullwhip effect, special condition, university governance